2018
DOI: 10.1111/pai.12969
|View full text |Cite
|
Sign up to set email alerts
|

Predictive values of alpha‐gal IgE levels and alpha‐gal IgE: Total IgE ratio and oral food challenge‐proven meat allergy in a population with a high prevalence of reported red meat allergy

Abstract: Alpha-gal allergy in a population with a high prevalence of reported red meat allergy showed a more rapid onset of symptoms than previously described and a high prevalence of isolated subjective gastrointestinal manifestations. Cutoff values are described for levels of sensitization to alpha-gal IgE and alpha-gal:total IgE ratio that are highly likely to result in clinically significant meat allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
100
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(109 citation statements)
references
References 31 publications
6
100
0
3
Order By: Relevance
“…In humans, anti-α-Gal IgE antibody levels (≥0.35 kU/L) have been identified like a risk factor for the development of the AGS (Commins et al, 2009;Van Nunen et al, 2009;Platts-Mills et al, 2015;Steinke et al, 2015;Galili, 2018;Cabezas-Cruz et al, 2019;de la Fuente et al, 2019;Hilger et al, 2019). Recently and albeit that cofactors are influential in the expression of mammalian meat allergy (Platts-Mills et al, 2020), Mabelane et al (2018) reported that anti-α-Gal IgE antibody levels higher than 5.5 kU/L are an indicator of AGS with 95% confidence. Herein we showed that zebrafish as humans do not synthesize α-Gal and produce natural anti-α-Gal IgM antibodies in response to gut bacterial microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, anti-α-Gal IgE antibody levels (≥0.35 kU/L) have been identified like a risk factor for the development of the AGS (Commins et al, 2009;Van Nunen et al, 2009;Platts-Mills et al, 2015;Steinke et al, 2015;Galili, 2018;Cabezas-Cruz et al, 2019;de la Fuente et al, 2019;Hilger et al, 2019). Recently and albeit that cofactors are influential in the expression of mammalian meat allergy (Platts-Mills et al, 2020), Mabelane et al (2018) reported that anti-α-Gal IgE antibody levels higher than 5.5 kU/L are an indicator of AGS with 95% confidence. Herein we showed that zebrafish as humans do not synthesize α-Gal and produce natural anti-α-Gal IgM antibodies in response to gut bacterial microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Galactose-alpha-1,3-galactose (alpha-gal) is a newly identified food allergen. Reactions to this allergen occur in 2 forms; delayed reactions after ingestion of beef, pork or lamb products, and immediate reactions after cetuximab exposure [78].…”
Section: Alpha-gal Allergymentioning
confidence: 99%
“…Based on these studies, along with case reports of IgE-mediated anaphylactic reactions to meat cropping up in areas outside the south, it is projected that mammalian meat allergy associated with lone star ticks will increase in future years. Multiple case reports have been further published describing the association between α-gal IgE and meat allergy in Central America ( 1 , 3 , 4 ), Europe ( 5 7 ), Australia ( 2 , 20 ), Asia ( 8 , 9 ), and South Africa ( 21 ). Ticks are endemic in all of these regions yet vary in species.…”
Section: Introductionmentioning
confidence: 99%